Trade Liberalization and Regional Inequality - Do Transportation Costs Impose a Spatial Poverty Trap? - Eduardo Haddad; Fernando Perobelli (European Regional Science Association (ERSA), 2005)
This paper focuses on the spatial impacts of barriers to trade, in the form of tariffs, in a national economy. More specifically, we are concerned with the spatial impediments for the internal transmission of the potential benefits of trade liberalization, in the form of high transportation costs that the more remote regions face. The strategy adopted in this research utilizes a spatial CGE model integrated to a geo-coded transportation model to evaluate shifts in the economic center of gravity and regional specialization in the Brazilian economy due to further liberal tariff policies. Comparative advantage is grasped through the use of differential regional production technologies; geographical advantage is verified through the explicit modeling of the transportation services, as well as increasing returns associated to agglomeration economies; and cumulative causation appears through the operation of internal and external multipliers and interregional spillover effects.
Keywords: 330